Efforts to Control the Prevalence of Drug Use Among School Children Using a Kie Approach - Sudirman, Sudirman; Saleh, Sitti Nurul Hikma; Subardin. AB, Subardin. AB; Sri Purwiningsih, Sri Purwiningsih (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2025)
ABSTRACT Drug abuse among students is an increasingly concerning issue that requires appropriate preventive intervention in school environments. This community service activity aims to increase students' knowledge about drugs through a Communication, Information, and Education (KIE) approach. The method used involved counseling sessions for junior high school students participating in Loru Village and Pombewe Village, Sigi District. The activity lasted for two days. The material was delivered through lectures, interactive discussions, and educational media such as slides and leaflets. Evaluation was conducted using pre-tests and post-tests to measure changes in participants' knowledge levels. The results showed a significant improvement in understanding across all aspects of the material, including types, impacts, and the dangers of drug use. In conclusion, the KIE approach has proven effective in enhancing students' understanding and has the potential to serve as a preventive strategy in efforts to control drug abuse among students. Keywords: Counseling, Drugs, KIE, Students